A late Holocene shift of typhoon activity recorded by coastal sedimentary archives in eastern China. Issue 2 (20th September 2021) - Yang, Yang; Piper, David J. W.; Normandeau, Alexandre; Zhou, Liang; Jia, Jianjun; Wang, Ya Ping; Gao, Shu
Abstract: Frequency changes in intense typhoons are of great concern to modern society. However, current understanding of the influence of climate on typhoon activity on the millennial scale is restricted by the sparseness of pre‐observational reconstructions in the north‐western Pacific. This study presents a 5500 year long typhoon record from the Jiangsu coast that provides the first >2 ka record in eastern China. Variations in the D90 grain size are the best predictor of recent typhoons in a second short high‐resolution core. Comparison with other typhoon records from south‐eastern China establishes a China millennial typhoon variability index during the middle to late Holocene, with maxima at ca 4750 ± 170, 3500 ± 220, 1500 ± 480 and 250 ± 170 yr bp and minima at ca 5200 ± 300, 4150 ± 430, 2600 ± 650 and 750 ± 270 yr bp . Peaks in typhoon activity in south‐eastern China (compared with Japan) correlate with damped (enhanced) El Niño–Southern Oscillation and weak (strong) East Asian Summer Monsoon, indicating a seesaw pattern in typhoon activity between the two regions. A shift in typhoon frequency pattern was also identified around 2000 yr bp in south‐eastern China, with subsequent more frequent typhoon activity. At that time there was sustained Atlantic Meridional Overturning Circulation reduction and its associated El Niño–Southern Oscillation enhancement, so Atlantic Meridional Overturning Circulation‐driven El Niño–Southern Oscillation changes are likely to be the major cause of the significant increase in typhoon activity since 2000 yr bp, resulting in the 1500 ± 480 and 250 ± 170 yr bp China millennial typhoon variability peaks. To accurately predict changes in intense typhoon activity, it is therefore important to understand how the Atlantic Meridional Overturning Circulation and El Niño–Southern Oscillation will respond to future climate change.